Penerapan Model Pembelajaran Problem Based Learning (PBL) untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis Siswa Kelas X SMA Kristen Kasih Kemuliaan pada Materi SPLTV - Maria Dea Pramudita; Lukita Ambarwati; Flavia Aurelia Hidajat (Departement of Mathematics Education, 2023)
This study aims to improve students' mathematical problem solving abilities using the Problem Based Learning (PBL) learning model on SPLTV material. The subjects of this research were class X SMA Kristen Kasih Kemuliaan West Jakarta, academic year 2022/2023. This type of research was Classroom Action Research (PTK) which was conducted in two cycles, namely cycle I and cycle II. The instrument used to measure students' mathematical problem solving abilities is student learning outcomes through a pre-test at the pre-cycle and post-test at the end of each cycle. The results of this study indicate that the application of the PBL learning model used with indicators of understanding the problem, discussing in groups to plan a solution, and explaining/checking the correctness of the answers obtained can improve students' problem solving abilities. This was proven by an increase in the percentage of students who were able to achieve the KKM obtained from the post-test in cycle I and cycle II compared to the results of the pre-test in the pre-cycle. In the pre-cycle the percentage of students who were able to achieve KKM from the pre-test results was 20.68%, the first cycle post-test results were 41.72%, and the second cycle post-test results were 86.20%. Thus the use of the PBL learning model can be used as a learning model to be applied to learning mathematics.